2012
DOI: 10.1111/cdoe.12000
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship of oral health status, swallowing function, nutritional status, and cognitive ability with activities of daily living in Japanese elderly people receiving home care services due to physical disabilities

Abstract: A lower number of teeth are positively related to swallowing dysfunction, whereas denture wearing contributes to recovery of swallowing function. Dysphagia, cognitive impairment, and malnutrition directly and indirectly decreased ADL in elderly people living at home and receiving home nursing care. The findings suggest that preventing tooth loss and encouraging denture wearing when teeth are lost may indirectly contribute to maintaining or improving ADL, mediated by recovery of swallowing function and nutritio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
171
4
14

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(201 citation statements)
references
References 32 publications
12
171
4
14
Order By: Relevance
“…Subsequently, this development entails more people in need of care. The literature reflects many oral problems of older people in need of care,1,2 while oral health of nursing home residents is considered even more compromised 35. A variety of factors seem to produce an increased likelihood of deterioration of oral health conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, this development entails more people in need of care. The literature reflects many oral problems of older people in need of care,1,2 while oral health of nursing home residents is considered even more compromised 35. A variety of factors seem to produce an increased likelihood of deterioration of oral health conditions.…”
Section: Introductionmentioning
confidence: 99%
“…These contributed to maintaining and improving activities of daily living, mediated by recovery of swallowing function and nutritional status. 39 This rare case of dialysis malnutrition makes the important point that uncommon causes of malnutrition such as BRONJ need to be considered in a patient with malnutrition on DOI: 10.3109/0886022X.2013.809005 hemodialysis. In that setting dental examination by a dental specialist may be required to make the definitive diagnosis.…”
Section: Discussionmentioning
confidence: 96%
“…Among them, a crosssectional study was begun to clarify the relation between edentulism and dysphagia and the relation between denture use and the improvement of swallowing function. 5 Furthermore, a physiological study revealed that the use of complete dentures has beneficial effects on swallowing. Wearing dentures could decrease the risk of laryngeal penetration, 8 stabilize swallowing movements, 9 stabilize tongue-palate contact, 10 shorten bolus pharyngeal transit time, 11,12 and improve bolus transport dynamics.…”
Section: Accepted Article Accepted Articlementioning
confidence: 99%
“…3 This decline also occurs in cases of edentulism owing to age-related oral changes and dental disease. 4,5 After the loss of many teeth, recovery of oral function through the use of complete dentures is often necessary in…”
Section: Introductionmentioning
confidence: 99%